Endothelial dysfunction in patients with Buerger disease - Igari K; Kudo T; Toyofuku T; Inoue Y (Vascular Health and Risk Management, 2017)
Kimihiro Igari, Toshifumi Kudo, Takahiro Toyofuku, Yoshinori Inoue Division of Vascular and Endovascular Surgery, Department of Surgery, Tokyo Medical and Dental University, Tokyo, Japan Abstract: We evaluated the endothelial function of patients with Buerger disease using peripheral arterial tonometry test, and examined the factors that are significantly correlated with the endothelial dysfunction in these patients. We performed the peripheral arterial tonometry test in 22 patients with Buerger disease. We recorded the patients’ characteristics, including ankle brachial pressure index and reactive hyperemia index, which reflect the endothelial dysfunction. We divided the patients with Buerger disease into the conservative treatment and lumbar sympathectomy group. While the reactive hyperemia index was not significantly different between these two groups, the ankle brachial pressure index was significantly different (1.12 versus 0.83, P=0.003). Furthermore, the reactive hyperemia index was significantly correlated with the ankle brachial pressure index value in the patients in the lumbar sympathectomy group (ρ=0.848, P=0.005). Given that patients with Buerger disease show impairment of the sympathetic nervous system, we should consider the after-effects of such an impaired system on the condition of these patients. The patients treated with lumbar sympathectomy might be more appropriate to evaluate their endothelial function by a peripheral arterial tonometry test. Keywords: peripheral arterial disease, Buerger disease, peripheral arterial tonometry, sympathectomy